PERANCANGAN KOMUNITAS VIRTUAL SEBAGAI IMPLEMENTASI CUSTOMER RELATIONSHIP MANAGEMENT (CRM) BERDASARKAN ATRIBUT KEBUTUHAN PELANGGAN DI AIRPHIBI TOUR & TRAVEL - Danar Bagaskoro (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2012)
AirPhibi Tour & Travel is a travel agency that always put the customer’s satisfaction ontop within every service they give. By considering the voice of customers, the company hasdiscovered some particular-internal details that could be evaluated and be improved to achievethe customer’s satisfaction in the future.By using the servqual method on the customer’s satisfaction problem, it’s been identifiedthat the gap score between the customer’s expectation (3.91) and perception (3.73) is -0.18. Thegap score itself signifies that the AirPhibi Tour & Travel service quality is nearly hit thecustomer’s satisfaction ideal value, which is 0 or more. The calculation of CustomerSatisfaction Index (CSI) gives result score 75.21, this index respresents that the AirPhibi Tour& Travel’s service quality is in the “Satisfying” range of customer’s satisfaction categories.From the analysis of the Importance Performance Matrix (IPM) categorization, there are 8points of customer’s requirements that subsequently will be developed in order to construct aQuality Function Deployment (QFD) matrix. They are online features development as thecompany’s information and transaction directory, domestic and international tour destinationoffering, railway travel and cruise ticketing service, notification of new information or specialevent, delivery service, request for a self-programmed tour, adding more branches in otherlocations, and membership system. The next phase is to develop those 8 points of customer’srequirements to QFD’s technical requirements. From developing each issue, it is obtained 19 oftechnical requirements, and the 19 points themselves need to be ranked based on eachimportance relative value. All of the QFD technical requirements should be aligned along with the company’sbusiness strategy. The company wants to implement the strategic objective in the same way asthe most logical and relevant business idea of Customer Relationship Management (CRM).Based on the focused technical requirements, AirPhibi Tour & Travel is able to vary theofferings, the services, the promotional programs, the messages, and the media. All of them canbe represented by developing and consolidating the online communication and informationsharing aspects. As the company manages to execute an expansion strategy in the futurecompetition, thus the most relevant CRM concept to carry out straightforwardly is e-CRM. Thisconcept leads to an idea of designing a virtual community under the AirPhibi Tour & Travel’sonline development focus. The AirPhibi.org forum is designed as the instrument of company’s e-CRM, with the purpose of having good relationship with the customers, retaining the customer’sloyalty, plus potentially gaining new customers.